On the reliability of multivariate biological distances in anthropology: critics and polemics - Piontek, Janusz (Anthropological Review, 1984)
The work contains a response to the views of M. Henneberg (published in Przegląd Antropol. 1984, 50, 65-80) on (1) cognitive value of the measures of geometrical distance, (2) the application of Penrose's method in anthropological studies, (3) testing the significance of differences between groups specified when Penrose's method is. used, (4) dependence between Penrose's distance and the number of samples, The present work contains also an answer to M. Henneberg's objections stating that the author of this polemics obtained research results by ‘manipulating’ with the empirical material. The present work criticizes and polemizes with the views of M. Henneberg. It states that M. Henneberg analyzed the views of different authors in a too onesided way, and regarding hte work of the present author he did not indicate any adequate facts evidencing the presumed ‘manipulation’ with the empirical material. In the conclusion, the work criticizes and polemizes with the views concerning the definition of biological distance. M. Henneberg believes that the distance should reveal the similarity in all possible features and he introduces the notion of a ‘general biological similarity’. On the other hand, the author of the polemics believes that anthropological studies consist in searches for similarities regarding a given class of features according to theoretical bases of biological taxonomy.